Artificial Intelligence in Islamic Law: Ethics, Governance, and Accountability - Enas Qutieshat; Majed Al Adwan; Maya Khater (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2026)
Muslim countries increasingly adopt Artificial Intelligence technologies, creating challenges related to accountability, explainability, discrimination, and oversight, while existing regulatory frameworks remain insufficient to govern high risk Artificial Intelligence systems comprehensively. This study examines the regulatory shortcomings of Artificial Intelligence governance in selected Muslim countries and formulates an Islamic governance framework based on the principles of Maqāṣid al Sharīʿah. The study applies normative legal research through statutory, comparative, and Islamic legal philosophical approaches to evaluate existing regulatory models and identify normative gaps. The analysis demonstrates three principal findings. First, existing regulatory frameworks do not adequately regulate explainability standards, algorithmic auditing mechanisms, judicial review procedures, and legal liability for automated decisions. Second, the widespread use of opaque algorithmic systems in digital surveillance, financial technology, and public administration increases the potential for indirect discrimination, unequal legal relationships, and disproportionate exercises of discretionary authority. Third, the principles of ḥifẓ al ʿaql, ḥifẓ al māl, and ḥifẓ al ʿird establish normative foundations that support explainability, meaningful human oversight, privacy protection, and economic justice within Artificial Intelligence governance.